Those Damned Immigrants : America's Hysteria over Undocumented Immigration - Román, Ediberto (Book collections on Project MUSE., 2013)
The election of Barack Obama prompted people around the world to herald the dawning of a new, postracial era in America. Yet a scant one month after Obama's election, Jose Oswaldo Sucuzhanay, a 31-year old Ecuadorian immigrant, was ambushed by a group of white men as he walked with his brother. Yelling anti-Latino slurs, the men beat Sucuzhanay into a coma. He died 5 days later. The incident is one of countless attacks that Latino/a immigrants have confronted for generations in America. And these attacks are accepted by a substantial number of American citizens and elected officials. Quick to cast all Latino/a immigrants as illegal, opponents have place undocumented workers at the center of their anti-immigrant movement, targeting them as being responsible for increasing crime rates, a plummeting economy, and an erosion of traditional American values and culture. In this book, the author takes on critics of Latina/o immigration, using government statistics, economic data, historical records, and social science research to provide a counter-narrative to what he argues is a largely one-sided public discourse on Latino/a immigration.